Health-related quality of life after otologic surgical treatment for chronic otitis media: systematic review - Schouwenaar, Esther M. M.; Hellingman, Catharine A.; Waterval, Jérôme J. (Frontiers in Neurology, 2023)
Objective: This systematic review aims to describe the impact of otologic surgery as treatment for chronic otitis media (COM) on the Health-Related Quality of Life (HRQoL) of adult patients.A literature search was performed in PubMed, Scopus, Embase and Web of Science till May 2023. Prospective studies including adult patients with COM (cholesteatoma) who underwent canal wall up mastoidectomy, canal wall down mastoidectomy or tympanoplasty without mastoidectomy, with pre-and postoperative HRQoL measurements, were considered eligible. Questionnaire validation studies were excluded. Risk of bias and study quality were evaluated with a Quality Assessment Tool (for before-after studies with no control group). To assess the change in HRQoL, pre-and postoperative HRQoL values and absolute changes were extracted, synthesized and presented in tables. Standardized mean differences (SMD) were calculated to enhance comparisons. Of the 720 studies identified, 16 met the inclusion criteria of this review. Different questionnaires were used throughout the studies. The CES and COMOT-15 were used by five studies and the ZCMEI-21 and COMQ-12 in three studies. All studies indicated statistically significant improvement in HRQoL from pre-to postoperative, measured with disease-specific HRQoL questionnaires. General HRQoL questionnaires did not show significant improvement. Calculated SMDs ranged from 0.31 to 6.99.Included studies had low (n=10) to high (n=6) risk of bias and poor (n=4), fair (n=7) or good (n=5) study quality. Surgical treatment positively impacts HRQoL of adult COM with and without cholesteatoma patients. However, clinical relevance of the reported changes is unknown due to the lack of the minimal clinically important differences (MCID) or cut-off values of each questionnaire. Therefore, further research regarding MCIDs of each questionnaire is needed. Future research should also report preoperative chief symptoms and indication for surgery to improve individual patient counselling.